On the present global distribution of R&D resources - Annersyedt, Jan (Vienna, Austria Vienna Institute for Development, 1979)
At present, the concentration of research and experimental development (R&D) to a small number of highly industrialized countries is one of the major features of global inequality.
Occasional paper 79/1
osc 21/10/2021
Loans
Keywords: Research and Development